A geografia em um contexto de crise científica e propagação de teorias conspiratórias - Andrade, João Vitor Nunes (2022)
This research examines the role of the internet and social media in the proliferation of conspiracy theories and misinformation, with a particular focus on the crisis of scientific authority and its implications for geographic science. The study, which is divided into three chapters, investigates the evolution of cyberspace, power dynamics in the digital sphere, and the rise of networked conspiracism, including conspiracies such as flat Earth theory, QAnon, and globalism. Ultimately, the research underscores the ways in which social media amplify political and social manipulation, arguing that Geography is a crucial tool for understanding and countering anti-scientific narratives, and promoting a critical and evidence-based discourse.